The Modification of The Delone and Mclean Model: System Quality, Information Quality, and Tax Literacy on E-Filing User Satisfaction - Faza Nisasilmi Nasuha (Jurnal ASET (Akuntansi Riset), 2023)
This study aimed to determine the effect of system quality, information quality, and tax literacy on the e-Filing system's user satisfaction among employees at the Universitas Pendidikan Indonesia (Indonesian University of Education-UPI). This study employed an explanatory survey method by collecting primary data in a questionnaire. The hypothesis testing of this study implemented simple linear regression analysis with the SPSS Statistics 25 software tool. The results of the study, it was found that  each variable which is system quality, information quality, tax literacy affect user satisfaction  e-Filing system at  Universitas Pendidikan Indonesia (Indonesian University of Education-UPI). Employees at Universitas Pendidikan Indonesia with PTNBH status have perception that e-Filing system's could be a benefit as taxpayersin in reporting SPT of the use e-Filing system. This study is expected to get insight of the e-Filing system. With this study could gain improvement of understanding in the use of e-Filing system at Universitas Pendidikan Indonesia (Indonesian University of Education-UPI). This study could evaluate the success of the e-Filing system uses model Delone and McLean by modifying several other variables.